EXTRACTION AND ANTIFUNGAL ACTIVITY OF TANNIN FROM TAMARIND HUSK - R.P.RAJADURAI JESUDOSS; N.VASANTHI; P.GAYATHRI (International Journal of Pharma and Bio Sciences, 2014)
Fungi are potent threat for food and tissue culture sector. Easy adoption and resistance of spores made fungus challenging to control. Natural antifungal agents are needed to control fungi in vegetables, foods, etc., in order to maintain foods natural character. In this study, we investigated the effect of various solvent crude Tannin extract (E) on the important food contaminating fungal agents like Aspergillus niger, Aspergillus flavus, Aspergillus nidulans and Aspergillus fumigatus. Tannin extracted from Tamarind husk using various solvents such as Cold water, Hot water, Acetone and Methanol (w/v) is used in this investigation. Antifungal activity was varied based on the solvent extract used, it was maximum in methanolic extract when compare to other modes of extraction. The crude methanol extract was purified by using column chromatography and the collected fractions were tested by ferric chloride test for the presence of tannin. We screened a maximum number of fractions and concluded that fraction 8th, 9th and 10th showed significant result were subjected for antifungal activity.